Evaluación bioeconómica de la suplementación con pellets de stylosanthes quianensis sobre la producción y constituyentes de la leche en vacas en pastoreo en la Zona Norte de Costa Rica - Alfaro-Blanco, Luis Francisco (Instituto Tecnológico de Costa Rica, 2015)
This work evaluate the effect of supplementation with two concentrated pellets of Stylosanthes guianensis (Legumix Premium and Supplement Alpha) versus two commercial concentrates (Vap-Feed and Predilecta) over the milk production and milk quality of grazing cows. The study was conducted in the San Isidro Farm´s, owned by the Alfaro Blanco family, located in the town of San Isidro de Sucre, district of Quesada, canton of San Carlos in the province of Alajuela, at an altitude of 1384 meters above the sea level, the temperature average is between 18 and 24 ° C, rainfall between 2000 and 4000 mm and classified as life zone of high humidity forest pre-montane, transition to rain forest. Nine cows were distributed under a change in design over repeated Latin square without extra period, with three squares, three cows per square and three periods (21 days each period, of which 14 were for adaptation and 7 measurements). For each period, within each square, each cow received different treatment. The results showed statistically significant differences (p<0.05) between treatments for milk production / cow / day (17.36, 15.46 and 15.00 for Vap-Feed, Legumix Premium and Suplemento Alfa respectively) .For the composition of milk, percentage of total solids (TS), fat (F) and lactose (L), no significant differences (p> 0.05) were found, between the Vap-Feed treatment and Legumix Premium treatment (TS 13.56, F 4.55 and L 4.82% Vap-Feed and TS 13.12, F 4.22 and L 4.69% Legumix Premium, respectively). For these variables statistically significant differences (p<0.05) between treatments based pellets of Stylosanthes were found (TS 13.12, F 4.22 and L 4.69% Legumix Premium and TS 13.92, F 4.87 and L 4.78% Suplemento Alpha, respectively). In the percentage of protein, significant differences between all treatments (p<0.05) were found (Vap-Feed 3.76%; Legumix Premium 3.57% and 3.79% Suplemento Alfa respectively). The partial budget economic analysis showed that supplementation with Vap-Feed treatment was higher income by 29% and 28%, respectively from the supplementation of Legumix Premium and Suplemento Alfa (3724, 2629 and 2672 colons / cow / day for Vap-Feed, Legumix Premium and Suplemento Alfa, respectively).
Proyecto de graduación (Licenciatura en Ingeniería en Agronomía) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Agronomía, 2015.
Keywords: Producción lechera; Nutrición animal; Pasturas; Calidad